Factors Associated with the Increasing Incidence of Congestive Heart Failure - Ambarsari, Nabilah; Kusumajaya, H. Hendra; Faizal, Kgs M. (Inspirasi Foundation, 2026)
Introduction: Congestive heart failure (CHF) is a serious cardiovascular condition characterized by the heart’s inability to pump sufficient blood to meet the body’s metabolic demands and remains a leading cause of morbidity and mortality worldwide. The prevalence of CHF continues to increase globally and in Indonesia, including Pangkalpinang City, with risk factors such as advancing age, gender, hypertension, and smoking contributing significantly to disease progression. The rising number of CHF cases at Depati Hamzah General Hospital highlights the need to identify factors associated with the increase in CHF incidence. Objective: This study aims to determine the factors associated with the increase in CHF at Depati Hamzah General Hospital, Pangkalpinang, in 2025. Method: The research method used was quantitative with a cross-sectional approach. A sample of 169 patients was selected using quota sampling. Data were obtained through questionnaires and medical records, then analyzed using the Chi-square test with a significance level of α = 0.05. Result: The results showed a significant association between age (p = 0.006), gender (p = 0.007), hypertension (p = 0.000), and smoking (p = 0.005). Conclusion: The conclusion of this study is that education about the factors of CHF plays a crucial role in preventing CHF from an early age. This includes consuming a healthy diet, exercising frequently/engaging in physical activity, quitting smoking, and regularly checking with the nearest health facility.